Development and testing of condensate assisted pre-cooling unit for improved indoor air quality in a computer laboratory. (October 2019) - Palanisamy, Dhamodharan; Ayalur, Bakthavatsalam Kannappan
Abstract: Ventilation of fresh air into an enclosed air-conditioned environment is often not sufficient leading to poor Indoor Air Quality (IAQ). This paper analyses the effective utilization of Air Conditioning (AC) condensate for improving the IAQ. A 33 TR cooling capacity is considered for the experimental study wherein the AC condensate recovered is 12.5 L/hr with an average temperature of 16 ± 0.5 °C. The pre-cooling unit (PCU) is designed for effective utilization of AC condensate. Fresh outdoor air is pre-cooled in PCU through Air to Water heat exchanger (AWhx) and Thermal Energy Storage (TES) before being admitted into the air conditioned space. Base case is one where no fresh air is admitted into the laboratory except through infiltration. In the base case, the numerical results of indoor CO2 concentration were compared with the experimental measurements. The error range was 0.5%–8%. In the modified case, 170 m 3 /hr of fresh pre-cooled air is admitted through PCU at 28 ± 0.3 °C. PCU helps in reducing the CO2 concentration inside the lab by 5%–6%. Further, the CO2 concentration is reduced by 42% up to 3 m from PCU and maintained below 1000 ppm for 1 h. The flow simulation was executed with a curtained control volume of 44 m 3 and the IAQ parameters were analyzed with six occupants. The CO2 concentration was maintained within 1000 ppm most of the time and the air velocity was also within the range of ASHRAE standard. Highlights: IAQ was found to be poor in four laboratories in terms of CO2 concentration. Pre cooling unit (PCU) was studied for effect on IAQ. CO2 concentration reduced by 42% at 3 m from PCU and maintained within 1000 ppm. Control room with air curtain model was simulated using SOLIDWORKS flow simulation. Experiments and simulation results confirm that PCU provides better IAQ.